Forensic applications and genetic characterization of Liaoning Han population revealed by extended set of autosomal STRs - Du, Jiang (Mol Genet Genomic Med, 2020)
BACKGROUND: Microsatellites or short tandem repeats (STRs) are considered the gold standard for forensic investigations and autosomal STRs are used for routine forensic personal identification. AIM: To provide a precise population database on an extended set of STRs which has never been done before and explore the forensic characteristics of 20 autosomal STRs. SUBJECTS AND METHODS: In the current study, we explored the genetic characteristics of 20 STRs loci in 1138 unrelated Han individuals using Goldeneye(®) 20A multiplex amplification system kit in the Liaoning Han population. Additionally, phylogenetic analysis based on the Nei's standard genetic distance was performed between the Han population and other relevant populations. RESULTS: A total of 253 alleles were observed while allelic frequencies ranged from 0.00043 to 0.5369. The combined discrimination power was 99.99999999999999999999789% and the combined exclusion power was 99.999998231%. Most of the loci were in HWE while only five pairs were out of LE. Population genetic analysis showed that the Han population has similarities with other East Asian populations. CONCLUSION: GoldenEye(TM) 20A kit detects high diversity in the Liaoning Han population. These STRs which are part of this kit can be used for forensic investigations. Population genetic analysis showed that the Han population is different from the minority populations of Xinjiang.